Arabic Quizzes Game to Improve Arabic Vocabulary - Putria, Annindita Hartono; Permatasari, Fira Eka; Hijriyah, Athiyah Laila; Mauludiyah, Lailatul (Universitas Muhammadiyah Sumatera Barat, 2021)
Learning media has experienced many variations along with the development of technology. Learning and playing are activities that are not only carried out by children but also by adults. Educational games as visual media are games that are packaged to support and increase users' thinking and concentration. The use of educational game technology in the teaching and learning process is an interactive learning technique. Mastery of Arabic vocabulary is very important, seeing from the many educational games that use this international language. This research was conducted to determine the effectiveness and benefits of educational games as well as learning designs using educational game content. In this study, researchers used quantitative methods that were supported by population and sampling. The development of this educational game was carried out by collecting data in the form of interviews as the main technique, documentation and observation as supporting techniques. The results in this study state that educational games are an effective and interactive medium in increasing Arabic vocabulary at the higher education level. This is because educational games can increase learning motivation and can make it easier for students to understand the material.